2021
DOI: 10.1108/yc-10-2020-1221
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary investigation of gamification from the young consumer’s perspective

Abstract: Purpose Over the past decade, gamification’s popularity has broadened into many industries and has become embedded in consumers’ lives. As privacy protection and how firms utilize users’ data has been at the forefront of consumers’ minds, practitioners and academics alike need to understand consumers’ perceptions of the ethics of gamification. This paper aims to explore and provide preliminary evidence on young consumers’ perceptions of gamification and the ethics involved in these strategies used by firms. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 86 publications
1
1
0
Order By: Relevance
“…Potgieter (2015) in South Africa and Ruiz-Del-Olmo and Belmonte-Jimenez (2014) in Spain. This also supports Hass et al (2021, p. 368) who found that university students have positive attitudes towards gamification in mobile apps and Wut et al (2021) who recommend adding gamification to “consumption-related mobile apps to increasing usage behavior”. As one participant said:…”
Section: Results Analysis and Discussionsupporting
confidence: 75%
“…Potgieter (2015) in South Africa and Ruiz-Del-Olmo and Belmonte-Jimenez (2014) in Spain. This also supports Hass et al (2021, p. 368) who found that university students have positive attitudes towards gamification in mobile apps and Wut et al (2021) who recommend adding gamification to “consumption-related mobile apps to increasing usage behavior”. As one participant said:…”
Section: Results Analysis and Discussionsupporting
confidence: 75%
“…The progress of gamification lies in its capacity to take advantage of the natural human craving for rivalry, accomplishment, and prizes, making banking exercises more charming and spurring for clients (Sheetal., et al (2022) [14]). As banks adopt gamification, they must also consider the ethical implications, such as safeguarding customer data and ensuring that gamified features do not inadvertently encourage risky financial behaviors (Hass, D., et al (2022) [15]).…”
Section: Review Of Literaturementioning
confidence: 99%